The Impact of English on Career Advancement - Afnesha Noveriana Chang; Rahma Dania; Mona Afersa (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This service is an activity of the Putra Indonesia University "YPTK" Padang lecturer team which aims to provide insight to high school and university students about how English can provide many benefits for academic life and future careers. This event carries the theme "The Impact of English on Career Development" and is held online. The aim of this activity is to increase awareness and interest in English among the younger generation and invite them to see English as not just a language, but as a communication tool that can open many paths in the future. The material is delivered via webinar where the presenter explains the benefits that students can gain by maximizing their English language skills. Apart from that, the service team also invited several students to become event committee members. Apart from that, workshop participants can ask questions related to the material presented to create a more in-depth discussion of the material. This activity is designed to increase the knowledge of the target community (in this case high school students and university students) so that they can maximize their learning and mastery of English for future careers.